ANALISIS LAGU TORAJA MARENDENG MARAMPA ARANSEMEN TINDOKI BAND - Lamba, Linesti; Ardini, Ni Wayan; Darmayuda, I Komang; Sumerjana, Ketut (Institut Seni Indonesia Denpasar, 2019)
This study aims to describe the musical form of Marendeng Marampa'